African placenames origins and meanings of the names for natural features, towns, cities, provinces, and counties - Room, Adrian (McFarland, 2008)
"This revised work has many expanded or entirely rewritten entries, increasing from 2,000 to more than 2,500 entries. Each entry identifies the country and, in most cases, geographical location. The name's origin and meaning follows, along with appropriate historical, topographical, and biological references. Cross references provide former names, alternate spellings, and alternate forms of current names"--Provided by publisher.